A66: Assessment of Radiographic Progression in Patients With Systemic Juvenile Idiopathic Arthritis Treated With Tocilizumab: 2‐Year Results From the TENDER Trial. Issue Volume 66:Issue(2014)supplement 3 (March 2014) - Malattia, Clara; Ruperto, Nicolino; Palmisani, Elena; Pederzoli, Silvia; Pistorio, Angela; Brunner, Hermine; Cuttica, Rubén J.; Calvo, Inmaculada; Garay, Stella Maris; Eleftheriou, Despina; Wouters, Carine; Wang, Jianmei; et al.
Abstract : Background/Purpose: A phase 3 trial (TENDER) demonstrated the efficacy of the interleukin‐6 receptor inhibitor tocilizumab (TCZ) in patients with systemic juvenile idiopathic arthritis (sJIA) (1 2 ). The aim of this study was to investigate the progression of radiographic joint damage in patients with sJIA treated with TCZ for up to 2 years in TENDER. Methods: One hundred twelve patients 2 to 17 years old with active, refractory sJIA of ≥6 months' duration and inadequate response to previous nonsteroidal anti‐inflammatory drugs and oral corticosteroids were enrolled in TENDER. Patients were randomly assigned 2:1 to receive TCZ according to body weight (12 mg/kg <30 kg or 8 mg/kg ≥30 kg) or placebo intravenously every 2 weeks for 12 weeks. Patients then received open‐label TCZ in the ongoing long‐term extension. Radiographic progression was calculated as change in adapted Sharp/van der Heijde score (aSH) score and/or Poznanski score, assessed on hand and wrist radiographs, from baseline to weeks 52 and 104. Radiographic progression was indicated by a positive aSH score change or a negative Poznanski score change. Clinical efficacy end points included American College of Rheumatology (ACR) Pediatric (Pedi) 70/90 responses. Results: Baseline and ≥1 postbaseline aSH and Poznanski scores were available for 47 and 33 patients, respectively (reasons for missing x‐rays: early withdrawal, no consent, unreadable x‐rays). Baseline characteristics for patients with radiographic data were similar in the whole TCZ population (1). Patients with assessable aSH/Poznanski scores had 5.2‐/4.8‐year disease duration, 21.3/19.2 active joints, 20.0/18.2 joints with limitation of movement, and 53.9/59.2 mm/h erythrocyte sedimentation rate. At weeks 52 and 104, 20 and 19 patients, respectively, had aSH progression, and 8 and 8 patients, respectively, had Poznanski score progression. Median changes in aSH score from baseline to weeks 52 and 104 were 0 and 0.5, respectively (1 ). Median changes in Poznanski score from baseline to weeks 52 and 104 were 0.29 and 0.16, respectively (1 ). Conclusion: Although changes in radiographic scores over time were seen in many patients, on average, patients with sJIA did not experience noticeable progression of radiographic damage over 2 years of treatment with TCZ.